Sawmilling in Sweden: Past, present and future - Tamrakar, Rijan (The Initiation, 2014)
With 62% of her land covered with forest, Sweden is the world’s second largest combined exporter of paper, pulp and sawn wood products. Modern industrial sawmilling of Sweden started from the mid-19th Century after British import was made liberal, and Norwegian exporters faced short supplies of raw materials and Canadian producers were more expensive. During the same time, Sweden also developed industries and technology making it more competitive. However, after 20th century, sawmilling in Sweden started to adopt ‘integrated forest firm approach’ where many small and locals sawmills were forced out of the business because of numerous war-crises and oil-crises that occurred. In recent decades production and exports from Sweden is in increasing trend. This increasing trend is the result of some specific strategies undertaken by Swedish sawmilling sectors viz. transforming market channel, transforming product value adding strategy and transforming service value adding strategy. Currently, Swedish sawmills can be categorized into nine groups based on their value addition strategy and technology they use. These sawmills face competition from other materials and countries, low efficient transfer of technology and knowledge transfer, presence of small scale sawmilling, and some sawmills are in risk as they lack of product diversification and have specialized production. Future of the sawmilling in Sweden is expected to be growing. However, they have to encourage the use of wood, transfer skill and knowledge, increase the size of the firm, further diversify the products, and also improve technology and mechanization. DOI: http://dx.doi.org/10.3126/init.v5i0.10260 The Initiation 2013 Vol.5; 110-120